Religious and Cultural Dialogue in The Betetulak Tradition in Pengadangan Village, Pringgasela District, East Lombok Regency - M. Mardyansyah (Tabéq Care Center and UIN Mataram, 2025)
Religion and culture are inseparable entities in society. The dialogue between the two has always been an interesting topic of study, giving rise to various views and assessments within society. The dialogical relationship between local culture and religion cannot be separated from the historical development of Indonesian society, particularly the Sasak community. This is particularly relevant to understanding the religious traditions practised by the community in Pengadangan Village in the Betetulak tradition. The Betetulak tradition is a combination of religious activities and local traditions practised for generations. In this study, the author uses a qualitative method. The primary sources are drawn from field observations, interviews, and documentation. Secondary sources were obtained from book quotations, documents, archives, and other records. The main topics discussed in this study are, first, how religion and culture are related in the betetulak tradition in Pengadangan Village, and second, what are the noble values of religion and culture in the betetulak tradition? Based on the results of the study, the relationship between religion and culture in the betetulak tradition is a combination of religious values (religious beliefs) and local traditions (local traditions) that are neatly arranged within the framework of the Sasak community’s beliefs, which are carried out with religious values (divine values) and cultural values reflected in the betetulak tradition (adat gama), which seeks to build a unified relationship that is always accompanied by religious attitudes in community life. The noble values underlying the implementation of this tradition include religious, cultural, social, tourism, and economic values.